Frequency of Endometrial Carcinoma in Patients Presenting with Abnormal Uterine Bleeding; A Cross Sectional Survey - Nazia Jabeen, Javeria Iqbal, Amara Saeed, Romasa Sarwar, Tamknat Ilyas, Maida Ilyas (Pakistan Journal of Medical & Health Sciences, 2022)
Background: PCOS, also known as polycystic ovary syndrome, is one of the most prevalent endocrine conditions. It is the root cause of abnormal menstrual cycles, including oligomenorrhea, amenorrhea, and dysfunctional uterine haemorrhage, among others. A relationship between polycystic ovary syndrome (PCOS) and endometrial cancer has been observed in previous research, which may vary over time due to continuously changing causative circumstances. Objective: To determine the frequency of endometrial carcinoma in patients presenting with abnormal uterine bleeding Methods: This was descriptive cross-sectional study in which 76 females of reproductive age were surveyed. The research was conducted the Link Medical Centre, Lahore between May to December of 2021. The data was analysed in SPSS 25.0, and it compared variables between normal and abnormal endometrial pathology, the independent samples t test were used. Results: The results regarding demographics showed that age and BMI were significantly higher in the abnormal (Age, M= 38.33, SD±1.74, BMI, M= 31.44, SD±2.09) endometrium group as compared to normal (Age, M=28.56, SD±1.81, BMI, M=24.37, SD±1.29, BMI) with a p value of 0.001 and 0.009, respectively. There were no significant differences (p value > 0.05) between the two groups when it came to the age of menarche and the thickness of the endometrium. The prevalence of endometrial polyp or carcinoma in abnormal bleeding was found to be 23.7%. Conclusion: The study findings showed that 23.7 precent patients with PCOS and abnormal endometrial bleeding have endometrial carcinoma. Moreover, there was no statical difference in endometrium thickness and age of menarche in both groups. Keywords: Endometrium Thickness, Endometrial Carcinoma, Abnormal Endometrial Bleeding, Endometrial Polyp